Double Jahn–Teller Distortion in AuGe Complexes Leading to a Dual Blue–Orange Emission. Issue 2 (15th December 2015) - Bojan, R. Vilma; López‐de‐Luzuriaga, José M.; Monge, Miguel; Olmos, M. Elena; Echeverría, Raquel; Lehtonen, Olli; Sundholm, Dage
Abstract: Invited for this month's cover are collaborators from the group of José M. López‐de‐Luzuriaga at Universidad de la Rioja, Spain and researchers from University of Helsinki, Finland. The cover picture shows a photograph of a gold–germanium complex that has two emission modes corresponding to two independent triplet excited states. Read the full text of the article at10.1002/cplu.201500337 . Abstract : "… We are interested in the detailed study of the photophysical properties of complexes displaying metallophilic interactions, particularly considering the relationship between the structure and the emissive properties… " Read more about the story behind the cover in the Cover Profile and about the research itself on page (DOI:10.1002/cplu.201500337 ).